Estabilidad oxidativa de la carne de llama (Lama glama) almacenada bajo refrigeración - Godoy, Mónica Daniela; Farfán, Norma Beatriz; Grigioni, Gabriela Maria (Asociación Argentina de Tecnólogos Alimentarios - AATA, 2024)
The objective of this work was to evaluate the effect of refrigerated storage of llama meat (Lama glama) on the oxidation of lipids, proteins and myoglobin and establish if there is a correlation between them. Worked with the Longissimus muscle dorsi. The piece was cut into 1 cm thick slices that were packed in plastic bags. food-safe low-density polyethylene (120 μm thick) and were stored at 4°C for 9 days. Lipid oxidation was determined using the method of substances reactive to thiobarbituric acid and was expressed in mg of malondialdehyde (MDA) per kg of meat, protein oxidation was determined based on the content of carbonyls and the oxidation state of myoglobin was determined from the proportions of their redox forms in an aqueous extract. The measurements were made on days 0, 2, 4, 7 and 9. As storage was prolonged, a significant increase (p<0.05) in the values ​​of MDA, carbonyls and proportion of metmyoglobin, which reached values ​​of 1.49 mg/kg of meat, 5.99 nmol/mg of proteins and 0.59 respectively on day 9. The increase in lipid oxidation was adjusted to a degree 2 equation, the carbonyl content had a growth exponential and the proportion of metmyoglobin did so linearly. The processes oxidation of lipids, proteins and myoglobin occurred simultaneously and the analysis Pearson's correlation test established a positive correlation between them. The values ​​of r were 0.9961 for the correlation between MDA and carbonyls, 0.9276 for MDA and metmyoglobin, and 0.9397 for carbonyls and metmyoglobin. From these From the results it was concluded that oxidative reactions favor each other. He Study of these interactions provides a basis to explain the deterioration of the call meat quality and subsequently develop strategies to maintain their sensory properties.